MANAJEMEN DAKWAH MAJELIS TABLIGH PIMPINAN WILAYAH MUHAMMADIYAH KALIMANTAN TIMUR - Tuzzakiah, Siti Nur Wahdah; Madani, Abubakar Idham; Amirullah, Amirullah; Dzakwan, Muhammad (Mushawwir Jurnal Manajemen Dakwah dan Filantropi Islam, 2023)
The process of implementing da'wah should have a good strategies, methods and management in order to produce quality of da'wah and achieve the predetermined goals of da'wah. Among the assemblies or institutions that oversee the field of da'wah are the Majelis Tabligh Pimpinan Wilayah Muhammadiyah, East Kalimantan. This research uses a type of field research, this is a research that collect data from interview, observation, and documentation. Based on the results of the research, planning the da'wah management of the Majelis Tabligh Pimpinan Wilayah Muhammadiyah of East Kalimantan includes determining the schedule, location, objectives, and activity budget. As for the organization of da'wah formed by structure and function as well as the division of tasks according to their respective fields. Furthermore, the mobilization of da'wah in management went well, the implementation of the da'wah program of the Majelis Tabligh, forming collaborations with various parties, providing guidance/motivation to the board of Majelis Tabligh and preachers. The practice of supervising da'wah in this case the chairman of the Majelis Tabligh provides formal oversight. This is the board of the Majelis Tabligh provides the results of the da'wah activities that have been carried out to the Pimpinan Wilayah Muhammadiyah. This institution has a responsibility to give an assessment, and provides non-formal oversight, by reprimanding members of the Majelis Tabligh who break the rules or are negligent in carrying out the trust. Keywords: Da'wah Management, Majelis Tabligh